EFIKASI HERBISIDA ATRAZIN TERHADAP PERTUMBUHAN GULMA DAN TANAMAN SERTA HASIL TANAMAN JAGUNG (Zea mays L.) - Zam Zami; Herry Susanto; Kuswanta Futas Hidayat; Hidayat Pujisiswanto (Universitas Lampung, 2021)
One of the herbicides that can be used to control weeds on corn cultivation is the atrazine herbicide. The aim of this study was to determine the effectiveness of atrazine in controlling weeds in corn, to determine whether there was a change in the composition of weeds in corn after application of the atrazine, and to determine whether the use of atrazine herbicide could cause phytotoxicity and inhibit growth and reduce corn yield. The research was conducted on farmer's land in Hajimena Village, Natar District, South Lampung Regency and Weed Laboratory, Faculty of Agriculture, University of Lampung from November 2019 to March 2020. The research was arranged in a randomized complete block design (RCBD) with four replications and six treatments, namely the herbicide atrazine doses of 1,20 kg/ha,1,80 kg/ha, 2,40 kg / ha, 3,00 kg / ha, manual weeding, and control. The results showed that atrazine herbicide doses of 1,20-3,00 kg/ha were effective to control of weeds total on corn area up to 6 weeks after application, atrazine herbicide caused change on weed composition of Richardia brasiliensis become Calopogonium mucunoides at 3 and 6 weeks after application, and the application of atrazine herbicide doses of 1,20–3,00 kg/ha did not cause phytotoxicity, inhibit corn growth, and decrease yields. Keywords: atrazine, weed, herbicide, corn